GRUP – Γ DUAL DARI SUATU GRUP–Γ - Sumanto, Y.D (MATEMATIKA, 2012)
On of can be considered as binary operation on . If there are such that is a group, then for any , is also a group and S called as . Otherwise for every element of can be considered as binary operation on . There are such that is - group and every is a group, troughout in this paper is called as dual group from